Hereditary chin trembling or hereditary chin myoclonus?. Issue 6 (1st December 1997) - Destee, A; Cassim, F; Defebvre, L; Guieu, J D
Abstract : Hereditary chin trembling is a rare autosomal dominant disease often considered as an "essential tremor variant". The clinical and neurophysiological data obtained in a new white family lead to the suggestion that this abnormal involuntary movement is a focal variant of hereditary essential myoclonus.